Perceptions of the primary health care team about the implementation of integrated care of patients with type 2 diabetes and hypertension in Slovenia: qualitative study - Nataša Stojnić; Zalika Klemenc-Ketiš; Majda Mori Lukančič; Črt Zavrnik; Antonija Poplas Susič (BMC, 2023)
Abstract Background Integrated care involves good coordination, networking, and communication within health care services and externally between providers and patients or informal caregivers. It affects the quality of services, is more cost-effective, and contributes to greater satisfaction among individuals and providers of integrated care. In our study, we examined the implementation and understanding of integrated care from the perspective of providers - the health care team - and gained insights into the current situation. Methods Eight focus groups were conducted with health care teams, involving a total of 48 health care professionals, including family physicians, registered nurses, practice nurses, community nurses, and registered nurses working in a health education center. Prior to conducting the focus groups, a thematic guide was developed based on the literature and contextual knowledge with the main themes of the integrated care package. The analysis was conducted using the NVivo program. Results We identified 12 main themes with 49 subthemes. Health care professionals highlighted good accessibility and the method of diagnostic screening integrated with preventive examinations as positive aspects of the current system of integrated care in Slovenia. They mentioned the good cooperation within the team, with the involvement of registered nurses and community nurses being a particular advantage. Complaints were made about the high workload and the lack of workforce. They feel that patients do not take the disease seriously enough and that patients as teachers could be useful. Conclusion Primary care teams described the importance of implementing integrated care for diabetes and hypertension patients at four levels: Patient, community, care providers, and state. Primary care teams also recognized the importance of including more professionals from different health care settings on their team.